2014
DOI: 10.1177/0333102414535111
|View full text |Cite
|
Sign up to set email alerts
|

Increased VIP levels in peripheral blood outside migraine attacks as a potential biomarker of cranial parasympathetic activation in chronic migraine

Abstract: Increased interictal VIP level measured in peripheral blood could be a biomarker helping in CM diagnosis, though it does not clearly differentiate between EM and CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 27 publications
8
63
0
1
Order By: Relevance
“…Results from animal studies have provided evidence for an antinociceptive effect of onabotA mediated by repressing the local stimulated release of a number of inflammatory mediators from sensory neurons, again including CGRP. 12,18,25,37 When taken together, these experimental findings and our current results suggest that the primary mechanism of action of onabotA in CM is the reversal of peripheral and central sensitization as a result of the inhibition of the release of CGRP 2,7,12,15 and to a lesser degree also of other pain-producing molecules, 11,28,40 by TVS neurons. This proposal also explains the absence of efficacy of onabotA in episodic migraine, 29 a condition where sensitization of central neurons has not occurred.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Results from animal studies have provided evidence for an antinociceptive effect of onabotA mediated by repressing the local stimulated release of a number of inflammatory mediators from sensory neurons, again including CGRP. 12,18,25,37 When taken together, these experimental findings and our current results suggest that the primary mechanism of action of onabotA in CM is the reversal of peripheral and central sensitization as a result of the inhibition of the release of CGRP 2,7,12,15 and to a lesser degree also of other pain-producing molecules, 11,28,40 by TVS neurons. This proposal also explains the absence of efficacy of onabotA in episodic migraine, 29 a condition where sensitization of central neurons has not occurred.…”
Section: Discussionsupporting
confidence: 72%
“…Although these findings in nonresponders could be explained by limitations of this study, such as the absence of a control group, the fact that most of these patients remained on oral preventives, the relatively low numbers of nonresponders in our series, or the intrinsic and subjective variability of migraine, our results might indicate that some patients with a "CM" phenotype could suffer from other headaches (eg, psychogenic, tension-type headache or other secondary headaches) in which CGRP does not seem to be involved. 3 Alternatively, as shown by measuring VIP or PACAP levels in this condition, 11,38 in some patients with migraine, pain could be secondary to a predominant activation of the parasympathetic arm of the TVS. 32,40,41 This could explain the fact that the efficacy of pure CGRP antagonists "gepants" seems to be lower than that seen for triptans, 28 which are known to inhibit both CGRP and VIP release by the TVS.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous infusion of VIP indeed caused vasodilation in the temporal superficial artery; however, it did not induce migraine attacks [97]. Interestingly though, a recent study has reported increased VIP levels in the serum of chronic migraine patients compared to healthy subjects [98]. In conclusion, we assume that VIP might have a strong vasodilator effect, but its role in initiating migraine attack is uncertain.…”
Section: Vasoactive Intestinal Peptidementioning
confidence: 64%
“…Cernuda-Morollón et al [183], for example, measured serum VIP levels in patients with chronic and episodic migraine. Their research showed consistent, significant elevations in serum VIP among test subjects that suffered with migraines.…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%